2019
DOI: 10.1536/ihj.17-742
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Specific Hollow Three-Dimensional Model for Simulating Percutaneous Occlusion of Patent Ductus Arteriosus

Abstract: Percutaneous catheter closure of patent ductus arteriosus (PDA) is difficult when the ductus is large and long or shows calcification. We created a patient-specific 3-dimensional (3D) model for PDA, with which we simulated device deployment, thereby selecting the device/size in a patient-by-patient manner. We assessed whether this 3D model is effective for catheter PDA closure. The 3D model was created in this institute, requiring 3 days and 90 US dollars. After its introduction, 7 consecutive patients (the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Valverde et al [9] extended the use of 3DPSP to the field of transcatheter cardiovascular interventions and reported 3DPSP being a valuable adjunct in planning and simulating endovascular stenting in transverse aortic arch hypoplasia. Following this approach, feasibility of 3DPSP to identify the optimal prosthesis in terms of size for transcatheter closure of atrial septal defect or patent ductus arteriosus was demonstrated [10,11]. Also, 3DPSP can enrich patient counselling [12][13][14] and affect clinical decision making [15].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Valverde et al [9] extended the use of 3DPSP to the field of transcatheter cardiovascular interventions and reported 3DPSP being a valuable adjunct in planning and simulating endovascular stenting in transverse aortic arch hypoplasia. Following this approach, feasibility of 3DPSP to identify the optimal prosthesis in terms of size for transcatheter closure of atrial septal defect or patent ductus arteriosus was demonstrated [10,11]. Also, 3DPSP can enrich patient counselling [12][13][14] and affect clinical decision making [15].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…This allows for better patient selection and appropriate selection of devices ahead of the procedure (32). Although PDA device occlusion is largely performed based on pre-procedural 2D echocardiography data alone or CT and CMR in some cases, 3D printing has been used for planning these interventions, allowing interventionalists to simulate and practice device deployment within the models themselves, thereby decreasing fluoroscopic and procedural times (33). In a surgical planning study, 3D visualization from static 3D printed models was found to improve understanding of anatomy and helped redefine the surgical approach in up to 47% of cases with complex congenital heart disease with significant modifications in 25% of cases (29).…”
Section: D Printingmentioning
confidence: 99%
“…Particularly in adult cases, the PDA can be long, tortuous, and calcified, which makes catheter-based device placement challenging. Matsubara and colleagues presented a case in which patient-specific 3D printed models were created to detail the precise anatomy of the proximal aorta, aortic arch, PDA, and pulmonary artery [22] . These models allowed for selection of a particular device and exact size.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…These models allowed for selection of a particular device and exact size. They also allowed the interventionalists to simulate and practice device deployment within the models themselves, thereby decreasing fluoroscopic and procedural times [22] . 3D models can be instrumental in decision making to determine feasibility of transcatheter intervention.…”
Section: Clinical Applicationsmentioning
confidence: 99%